The Structure of Labor Market as an Indicator of Shadow Economy - Gerasymenko, S. S. (Statistics of Ukraine, 2021)
The article is focused on analysis of factors that determine the patterns of market economy operation. Ukraine, like the other world, has witnessed more than one financial and economic crisis since it gained independence. Its manifestations are the reduced GDP, the worsened financial performance in the business sector, the shrinking real income of the population and the declining investment activity. Search for the factors provoking crises and ways to mitigate their effects has been a central subject of studies conducted by many researchers. However, their research effort has not paid adequate attention to analysis of causal links between the so called shadow economy and the parameters embedded by researchers in models of the modern economy. Methods for shadow economy assessment are author-specific, with quite distinct momentary results. Also, an analysis of shadow economy trends has been virtually lacking, which does not allow to account for its contribution in the formation of market economy patterns, although it seems to be quite significant given a large share of the shadow economy sector at national and global level. The possibility for assessment of the shadow economy in its relation with the labor market structure that can be characterized by developed robust models is substantiated. Apart from description of the current labor market performance, it also allows for its forecasting. Hence, the elaboration of measures aimed to improve the situation on the labor market enables to reduce the share of shadow economy and, considering the other factors, to halt the occurrence of economic crisis or mitigate its effects for the economy and public welfare. The main problem that have limited so far the application of the abovementioned approach to solving the problems of economic forecasting was lack of consensus about the classification of the economic system components as either factors or results. This article is an author’s attempt to demonstrate that the structure of labor market and the share of unemployment in particular, is largely dependent on the role of shadow sector in the domestic economy. By employing models characterizing unemployment, this allows to determine the share of its variation related with the shadow economy, and to proceed with forecasting the share of shadow sector in the economy and its impact on the formation of the national economy patterns. Determining the measure and direction of this impact on a domestic economy has to be the next phase of the study.